A Geoportal Supporting Spatial Planning in Poland: Concept and Pilot Version - Michalik, Anna; Zwirowicz-Rutkowska, Agnieszka (Geomatics and Environmental Engineering, 2023)
Due to the complexity of planning processes, as well as the desire to satisfy stakeholders and entities involved in spatial development and planning procedures, there is a clear need to create a platform for managing spatial development planning information. The aim of this paper is to present a project and pilot version of an urban platform (spatial planning geoportal), which is intended to be a solution used for the creation, analysis, and presentation of spatial data related to spatial planning. To implement the concept of the geoportal, one of the models used in systems and software engineering known as incremental execution was used, together with the language for documenting phases of an IT project – the Unified Modeling Language (UML). The concept includes a formal description of the geoportal functionalities using UML as well as the perspective of solution users and stakeholders. This paper also shows the functionality of the pilot version of the geoportal, which refers to spatial planning at the local level and local spatial development. The spatial planning geoportal presented in this paper adheres to the reform of spatial planning and is intended to help in conducting spatial policy, both at the local and central level. Establishment of the spatial planning geoportal may contribute to increasing the efficiency and quality of the spatial planning system in Poland, as well as other areas such as management of local government units, local and regional transport, and regional planning.